Design Evaluation of Commercial Websites of India - Hussain, Mubashir; Manhas, Jatinder (International Journal of Computer Sciences and Engineering, 2018)
Design of the commercial websites is a crucial and important factor that should be considered for improving its effectiveness, efficiency and satisfaction w.r.t services to citizens [1]. In this study the effectiveness of various design parameters (such as page size, composition, download time etc.) on commercial website will be analyzed by taking into considerations different website development standards recommended for them. The aim of this study is to analyze different commercial Website by testing their existing design with the help of design evaluation tool developed for the purpose to understand their deviations from the standards and to evaluate their performance with respect to the parameters considered by the tool. The results indicated that there is an urgent need to improve the design features of commercial websites in order to be more effective and user-centric. The authors took 20 commercial websites of India, analyze their different parameters and on the basis of analysis show their overall compliance with the standards and guidelines. With the help of the results obtained a graphical analysis of the websites is made by the authors that determine the effect of these parameters on the efficiency and accessibility of the commercial websites.